MODEL VEKTOR AUTOREGRESSIVE UNTUK PERAMALAN CURAH HUJAN DI INDRAMAYU (Vector Autoregressive Model for Forecast Rainfall In Indramayu ) - Dewi Retno Sari Saputro; Aji Hamim Wigena; Anik Djuraidah (FORUM STATISTIKA DAN KOMPUTASI, 2011)
There  are  three  regions  of  rainfall  that  has  been  formed,  each  rainfall  regions has a variety of homogeneous and there is a correlation between rainfall stations. In  each  region  can  be determined  rainfall  prediction  model simultaneously.  The model  is  a  model  of  Vector Autoregressive  (VAR)  which  is  an extension  of  the autoregressive  model  (AR).  Based  on  this  research,  we  can  determine  the  VAR model by lag 1 or VAR (1) for each region. Region 1 (Anjatan and Sumurwatu), region  2  (Salamdarma  and  Gantar)  and  region  3  (Kedokan  Bunder  and Sudimampir), each of which has a Root Mean Square Error Prediction (RMSEP) of  3.93;  5:03;  4:48;  5.3;  2:18  and  3:53.  Correlation  value  of  observations  with predictions of rainfall respectively, 0.71; 0.62; 0:57; 0:59; 0.89, and 0.91.  Keywords: AR, VAR, RMSEP, correlation